Mengukur Kondisi Kesehatan Keuangan melalui Analisis Rasio Keuangan Perusahaan PT Waskita Karya (Persero) Tbk - Situmorang, Dokman Marulitua (Universitas Kristen Wira Wacana Sumba, 2024)
According to Kepmen BUMN No.: KEP-100/MBU/2002 concerning the assessment of the level of financial health of the BOMN, the research entitled â€œAnalysis of the health level of the POMN based on the financial aspects of P.T. Waskita Karya (Persero) Tbk in the year 2018-2022â€ aims to determine the financial health using the calculation of eight ratio indicators on the limited association of the WSKT (persero) tbk of 2018-2022. The method of this research is to use narrative descriptive methods in the form of case studies using a quantitative approach. The object of the study is the Financial Report of the WSKT Limited Associations (Persero) Tbk for the year 2018-2022. The results of the research indicate that the health status of the BUMN in the TBK from 2018 to 2022 is 80, 57, 25, 46 and 49. In 2018, PT Waskita Karya (Persero) Tbk obtained category A using Healthy Predicate. In 2019, obtaining category BBB using Less Healthy predicate. However, in 2020 obtains category CCC using Non-Healthy category and in 2021 to 2022 obtain the category BB using Lesser Healthypredicates. A limited company is required to raise its financial health so that it can get a healthy AAA rating by increasing its financial performance.